Synthesis and biological evaluation of cadiolide analogues, thiobarbituric acid and pyrimidine derivatives - Muhammad Shabeer (2019)
The present thesis describes a study towards the development of alternative methodologies for the synthesis of a wide spectrum of pyrimidine derivatives. The targeted pyrimidine scaffolds have been known for their immense biological, medicinal as well as synthetic values. Almost all of the synthesized compounds are found to be novel. Preliminary screening towards the antimicrobial and anti-urease activity of some selected pyrimidine derivatives have also been performed and covered in the thesis. A bismuth nitrate catalyzed Knoevenagel condensation between thiobarbituric acid and aromatic aldehydes has afforded the derivatives 1-20 in excellent yields (81-95%). Theantimicrobial activities of compounds 1-20 were evaluated against two filamentous fungi (Alternaria solani and Fusarium solani), one bacterium (Erwinia carotovora) and six yeast strains of clinical importance (Candida albicans, C. tropicalis, C. parapsilosis, C. lusitaniae, C. dubliniensis and Cryptococcus neoformans). The IC50 for each strain was determined andthis class of compounds showed promising activity against the yeasts. The activities were comparable, in some cases, to that found for the commercial antimicrobial drugs nystatin and miconazole. Most of the compounds presented IC50 <1.95 g mL-1 towards at least onemicrobial strain, and some of them were selective microbe inhibitors. Minimum inhibitory concentration (MIC) was determined against the two pathogenic fungi, A. solani and F. solani. The compounds showed activity exclusively against A. solani confirming their selectivity as antimicrobial agents. Compounds 5 and 14 at 3.90 g mL-1 were able to completely stop A. solani growth under the assays conditions. The selectivity and potent activity of the compounds points this class as a promising source of novel antimicrobial agents. Thiobarbituric acid derivatives also showed good anti-urease inhibitory activity with inhibition values of 48.66 - 69.92% at 40M in 1% Tween-20. Amongst the series compound 8, 12 and 18 showed better activity with MIC values of 63.18, 69.40 and 69.92%.Synthesis of 2-amino-4,6-dihydroxypyrimidine (ADHP) derivatives with different moieties were performed to explore their biological profile. The 2-amino-4,6-dihydroxypyrimidine (ADHP) was obtained in yield higher than 90% by a ring closing reaction. A reaction of ADHP with different aldehydes in the presence of NaOH afforded Schiff bases in 92-96% yield. Schiff bases of ADHP were prepared and screened for theirputative urease inhibitory activity. All of the synthesized compounds showed good antiurease activity with inhibition range of 59.09 - 84.76% at 40ML-1 in 1% Tween-20 solution. Compounds 23, 27 and 28 were the most potent among the series with inhibition ranges of 81.54, 80.70 and 84.76% respectively. These could serve as lead substances for thedevelopment of novel synthetic compounds with enhanced inhibitory ureolitic activity. Several studies have shown that the number of biotypes of resistant microorganisms is increasing and the search for new substances with new mechanisms of action becomes a necessity. In this context, the cadiolides deserve attention, as they present potent antibacterial activity and low cytotoxicity. In this sense, in the present work is presented the synthesis of the cadiolides by Diels-Alder cycloaddition cycloreversion reaction. The synthesis of the analogs to the cadiolides was carried out in four to five steps from the keto-alkynes, obtainedby the Sonogashira cross coupling reaction with different acid chlorides or by the condensation reaction with an aldehyde, followed by oxidation reaction. The synthesized compounds were submitted to biological assays to evaluate their antimicrobial properties against Staphylococcus aureus, Escherichia coli, Salmonella. typhimurium, Bacillus cereusand Candida albicans. In general, the results of the bioassays showed that all compounds evaluated in the concentration of 128 µg/mL showed low antimicrobail activity for all the compounds tested except 68 which shows above 50% inhibition against B. cereus. IC50 values were also determined for Compound 68, which shows comparable activity with thepositive control with IC50 value of 0.19 m mL-1.